The Relationship between brain-behavioral systems and cluster B personality disorders by mediating dark traits of personality - Ghasemzadeh, Ramin; Mahmoudalilou, Majid; Bakhshipour Roudsari, Abbas; Bayrami, Mansour (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: It seems that one of the important influencing factors in cluster B personality disorders is brain-behavioral systems and dark personality traits, so the purpose of the present study is the relationship between brain-behavioral systems and cluster B personality disorders with the mediation of dark personality traits. Methods: The design of this research was a correlation method in terms of applied purpose and in terms of controlling variables. The statistical population of the study was all students of Tabriz universities in the academic year 2021-22, of which 450 people were selected by cluster random sampling and studied. For data collection, the Dark Dimensions of Personality Questionnaire, the revised Jackson Strengthening Sensitivity Scale, and the Millon Multi-Axis Clinical Test were used. Data were analyzed using Pearson correlation coefficient and path analysis. Results: The results showed that there is a positive relationship between behavioral activation system and cluster B of personality disorders. There is also a negative relationship between behavioral inhibition system and cluster B personality disorders. There is a positive relationship between dark personality traits and dramatic personality disorder. There is a negative relationship between behavioral inhibition system and war and escape with the dark trait of Machiavellianism. Conclusion: The results of this research show that paying attention to the variables of behavioral brain systems and dark personality traits play an important role in personality disorders.